Enhancing Learning Motivation and Self-Efficacy: Implementing the ARCS Flipped Classroom Strategy with Nearpod LMS - Taufiq Lilo Adi Sucipto; Ida Nugroho Saputro; Rifchelda Shevanda Ragesta (AL-ISHLAH: Jurnal Pendidikan, 2025)
The COVID-19 pandemic has brought significant disruptions to education, leading to decreased student motivation and self-efficacy. In response, this study investigates the use of Nearpod, a Learning Management System (LMS), to improve achievement motivation and self-efficacy among Grade XII DPIB B students at SMK Negeri 2 Surakarta.This classroom action research was conducted in two cycles, employing the ARCS Flipped Classroom strategy integrated with Nearpod LMS. Data were collected through validated questionnaires measuring students' achievement motivation and self-efficacy across three phases: pre-action, Cycle I, and Cycle II.Findings revealed a consistent increase in both achievement motivation and self-efficacy. The average achievement motivation scores rose from 39.44 (pre-action) to 45.80 (Cycle I) and 48.36 (Cycle II). Similarly, self-efficacy scores improved from 40.67 (pre-action) to 45.08 (Cycle I) and 48.5 (Cycle II). These improvements indicate the effectiveness of Nearpod LMS in enhancing students' psychological engagement in learning.The implementation of Nearpod LMS, combined with ARCS and flipped classroom elements, significantly improved students’ motivation and self-efficacy. The flexibility and interactivity offered by Nearpod support its continued use in post-pandemic education. This research underscores the potential of technology-based instructional strategies in classroom settings and provides a model for teachers to adapt digital tools to foster student engagement and confidence across various educational levels.